Compatibility between agendas for improving human development and wildlife conservation outside protected areas: Insights from 20 years of data. Issue 3 (1st August 2019) - Ament, Judith M.; Collen, Ben; Carbone, Chris; Mace, Georgina M.; Freeman, Robin
Abstract: The UN Sustainable Development Goals (SDGs) include economic, social and environmental dimensions of human development and make explicit commitments to all of life on Earth. Evidence of continuing global biodiversity loss has, at the same time, led to a succession of internationally agreed conservation targets. With multiple targets (even within one policy realm, e.g. the CBD Aichi Targets for biodiversity), it is possible for different indicators to respond in the same direction, in opposite directions or to show no particular relationship. When considering the different sectors of the SDGs, there are many possible relationships among indicators that have been widely discussed, but rarely analysed in detail. Here, we present a comparative cross‐national analysis exploring temporally integrated linkages between human development indicators and wildlife conservation trends. The results suggest that in lower income countries there are negative relationships between measures of human population growth and bird and mammal population abundance trends outside protected areas. The results also suggest a positive relationship between economic growth and wildlife population trends in lower income countries. We stress, however, the need for future research to further explore the relationships between economic growth and natural resource‐based imports. Our results highlight a clear potential for compatibility of the conservation and development agendas and support the need for further integration among sustainable development strategies. A freePlain Language Summary can be found within the Supporting Information of this article. Abstract : A freePlain Language Summary can be found within the Supporting Information of this article.